ANOMALI IKLIM, EVALUASI MASA TANAM, TINGKAT KEHILANGAN HASIL DAN PENGATURAN SISTEM PRODUKSI PERTANIAN DI KALIMANTAN TIMUR - Surmaini, Elza; lrianto, Gatot (Research Center for Biology-Indonesian Institute of Sciences, 2003)
Water availability generally enhanced accumulation crop productivity in short time caused yield accumulation in that period. El-Nino, a climate phenomenon that increased of intensity and frequency lately caused planting period determination is being more important in minimizing agriculture risk like El-Nino. El-Nino impact on season displacement and rainfall drop were carried out with weighted regression between anomaly of rainfall and sea surface temperature (SST). Then, the information use to quantify rainfall fluctuation in relation with SST. Rainfall forecasting for next 3-6 month used in evaluation of planting period and then recommend some scenario with different level yield loss.Result showed that rainfall in north-side of East Kalimantan not affected by SST, but in south-side the correlation was significant. Especially El-Nino 1997 has forwarded dry season and delaied wet season.Analysis of planting period on dry season showed that paddy, corn, and tomato had high yield loss caused by water stress.Cropping pattern and planting period modification were required to suppress the yield loss. One alternative was by implementing runoff and rainfall harvesting to avoid yield accumulation only in wet season. Conventional cropping pattern that rely on rainfall should be managed in to whole area, so that quantity and continuity of yield may be able to be optimized.